10 - Book Reviews: Sustainable Development in Third World Countries: Applied and Theoretical Perspectives. Edited by Valentine Udoh James, Westport, Connecticut, Praeger, 1996, xvi + 245p. - Zeleza, Paul Tiyambe (Africa Development, 1998)
Abstract